Sistem Pelayanan Kecamatan Mejobo - Evanita, Evanita; Dahlan, Mohammad; Susanto, Arief; Nindyasari, Ratih; Ghozali, Muhammad Imam (Intimas, 2024)
The administrative process has gradually shifted from manual to computerized administrative processes in various public service activities. The service team then carried out observations in the villages of Mejobo sub-district which turned out to still be very lacking in the need for data processing and computerized information coverage. For this reason, the Service Team is trying to implement the system that is already running in Janggalan in 11 villages in Mejobo sub-district. This system consists of various processing of population data, basic family infrastructure, socio-economic conditions, access to education, etc. This system will later bridge the interests of the village government in producing data and information as well as in reporting to the local government. The system is expected to be able to support the reporting system to local governments by presenting and providing data recapitulation with appropriate indicators. This implementation is carried out using training and mentoring service methods for government staff in Mejobo villages which will then be continued with the community.